2022
DOI: 10.3233/jad-215504
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloidogenic Nanoplaques and Cytokines in Alzheimer’s Disease: Pilot Study in a Small Naturalistic Memory Clinic Cohort

Abstract: Background: Neuroinflammation is a central component of Alzheimer’s disease (AD) and correlates closely with amyloid pathology. Markers of inflammation such as cytokines, and amyloidogenic aggregates, so-called nanoplaques, are both promising biomarker candidates for AD. We have previously shown that there is a relationship between the levels of nanoplaques and cytokines in cerebrospinal fluid, but it is unknown whether this association extends to serum. Objective: Investigate in a naturalistic memory clinic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…IL-8 was also associated with the accumulation of pathological proteins characteristic of AD [88,89]. Lower levels of Aβ40 and Aβ42 and higher levels of IL-8 were associated with more severe cognitive decline [88][89][90].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…IL-8 was also associated with the accumulation of pathological proteins characteristic of AD [88,89]. Lower levels of Aβ40 and Aβ42 and higher levels of IL-8 were associated with more severe cognitive decline [88][89][90].…”
Section: Discussionmentioning
confidence: 98%
“…IL-8 was also associated with the accumulation of pathological proteins characteristic of AD [88,89]. Lower levels of Aβ40 and Aβ42 and higher levels of IL-8 were associated with more severe cognitive decline [88][89][90]. Positron emission tomography (PET) research indicated negative associations of Aβ with cerebrospinal fluid (CSF) IL-8 levels in the areas where early Aβ accumulation occurs (in the lateral and medial frontal lobes) [91].…”
Section: Discussionmentioning
confidence: 99%
“…There are also examples of how predefined cytokine panels have been used for serum analysis in the context of PD ( 79 ) and complement factors in plasma in search for FTD-associated profiles in samples from the GENFI consortium ( 80 ). In one study, a custom-designed panel was assembled based on initial analysis of a predefined set of proteins and evaluated in serum samples from an AD cohort ( 81 ). The single binder assay has been applied to perform large-scale analysis of both CSF and plasma/serum in the context of AD ( 82 , 83 ), FTD ( 84 , 85 ), ALS ( 86 ), and for the analysis of CSF protein levels in cognitively healthy individuals ( 87 ).…”
Section: Applications In Researchmentioning
confidence: 99%